Incidence of diseases and selection of soybean cultivars (Glycine max l. Merril) in a water deficit environment - Goi, Renato José; Carvalho, Ivan Ricardo; Loro, Murilo Vieira; Pradebon, Leonardo Cesar; Silva, Thayane Beck da; Frantz, Vitor Rott; Sand, Arthur Ledermann Van Der; Ferreira, Luiz Leonardo (Revista de Ciências Agroveterinárias, 2024)
This work aimed to verify if it is possible to select soybean genotypes tolerant to diseases and water stress. The experimental design was randomized blocks (RBD), with thirty soybean genotypes, in four replications, totaling 120 experimental units. Evaluations were performed based on crop yield components and disease incidence in thirty soybean cultivars in field conditions. Analysis of variance was performed at 5% probability using the F test. Variables that showed significance were compared using Scott-Knott's grouping of means at 5% probability. Pearson's linear correlation coefficients were calculated between pairs of variables, with significance imposed by the t test at 5% probability. The Euclidean distances were calculated and the UPGMA grouping was performed to construct the genetic dissimilarity dendrogram, after which the biplot principal components were used to identify the association trend between variables and cultivars. It was possible to select soybean genotypes for grain production and disease tolerance in an environment with water stress. Cultivars M 5947 IPRO, TEC 6702 IPRO, M 6410 IPRO showed the highest grain yield. The cultivar TEC 6702 IPRO showed the best agronomic performance for morphological and productive characteristics, associated with the lowest incidence of diseases.